2009
DOI: 10.1021/jp8115116
|View full text |Cite
|
Sign up to set email alerts
|

Saturated Orientational Polarization of Polar Molecules in Giant Electrorheological Fluids

Abstract: Many researches on polar-molecular electrorheological (PMER) fluids with giant electrorheological effects were reported in recent years. The particles of PMER fluids (PMER particles) are known to have a dielectric core with high dielectric constant and a shell of polar molecules. Our calculation of local electric fields using the finite element approach shows that the local electric field can cause an orientational polarization of the polar molecules. The saturation of the orientational polarization occurs on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…The resulting electrical energy density yields an excellent account of the observed GER yield stress variation as a function of the electric field. Electrorheological (ER) fluids [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] are a type of colloidal dispersions which can vary their rheological characteristics through the application of an external electric field. The traditional ER mechanism is based on induced polarizations arising from the dielectric constant contrast between the solid particles and the fluid [6,12].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The resulting electrical energy density yields an excellent account of the observed GER yield stress variation as a function of the electric field. Electrorheological (ER) fluids [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] are a type of colloidal dispersions which can vary their rheological characteristics through the application of an external electric field. The traditional ER mechanism is based on induced polarizations arising from the dielectric constant contrast between the solid particles and the fluid [6,12].…”
mentioning
confidence: 99%
“…Moreover, as the GER effect is highly sensitive to whether the dispersing oil can wet the solid particles [10,11], in contrast to the traditional ER fluids, a natural question is how this observation can be integrated into a coherent GER mechanism. In view of the fact that the GER effect has now been reproduced in many different material systems and therefore is becoming a much more general effect [14,15], answers to the above questions would not only be timely, but may also shed light on how to devise general strategies for harnessing and controlling the large electric energy stored in molecular dipoles.In this work we use molecular dynamics (MD) simulations to show that in a mixture of urea molecules with silicone oil chains confined between two bounding surfaces (denoted as substrates below) of a nanoscale contact, aligned urea molecular dipoles can form filaments snaking through the pores of the oil film to bridge the substrates. The required electric field for aligning the urea dipoles is found to be lowered by a factor of 2 to 3 in the presence of the oil chains, compared to that without the oil chains.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The polarization of molecular dipoles in the contact region between two neighboring nanoparticles is thought to be responsible for the GER effect. [15][16][17] Various inorganic and organic/inorganic GER materials have been synthesized; [18][19][20][21][22][23][24][25][26][27] for example, Wen et al 18 reported a new type of GER fluid consisting of polar group-modified nano-sized barium titanyl oxalate particles suspended in silicone oil.…”
Section: Introductionmentioning
confidence: 99%